Visual guide to Elliott Wave trading - Gorman, Wayne; Kennedy, Jeffrey (Business writer) (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
The Visual Guide to Elliott Wave Trading is an in-depth, easy-to-use guide to trading the financial markets with the Elliott Wave Principle. In many ways this book picks up where Frost & Prechter's classic Elliott Wave Principle: Key to Market Behavior left off, which makes it ""required reading"" if you want to build a solid foundation in Elliott wave analysis. Co-authored by two of Elliott Wave International's most trusted analysts -- Wayne Gorman and Jeffrey Kennedy -- their trading insights offer a perfect blend of traditional textbook and real-world application.
The anatomy of Elliott Wave trading -- How zigzags and flats set up a trade for the next impulse wave -- How a triangle positions you for the next move -- Riding Wave C in a zigzag
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Speculation; Stocks; Elliott wave principle; BUSINESS & ECONOMICS -- Investments & Securities -- General; Elliott wave principle; Speculation; Stocks; Electronic books